Mejoramiento de la línea de producción de fabricación de pallets mediante el estudio de trabajo en la empresa tropical pallets del cantón Quevedo - Taipe Chingo, Luis Fredy (2020)
This research project was carried out in the company Tropical Pallets, with the aim of improving the production line in the manufacture of pallets through the study of work, for this is done a study of all the elements involved in the area production as; machines and equipment, operators and jobs, which in relation to all these elements can cause production delays and possible accidents at work. The objective of applying a work study will allow us to determine how the work is carried out in each process, also helps us to determine standard times, to obtain favorable results in contrast to normal time, eliminating lost times and possible bottleneck. By direct observation to the production area, it was possible to find that there is a poor distribution of equipment and machinery at unnecessary distances that this delays production, the poor placement of waste and finished products that makes it difficult easy mobility between different stages of production. For the development of this problem is made use of study tools such as; flowcharts, route diagram, analytical diagram and graphs that allow you to determine the current situation of the company. In addition, the review of theoretical and conceptual bases that allow us to have a broader knowledge for the development of research results and discussion, which will help to establish the conclusions and recommendation of the research Developed. Key words: Working study – standard time – production line – distribution